Kebersahajaan Ekspresi dan Makna Karya Sastra Mustofa Bisri - Redyanto Noor (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The simplicity of the expression and meaning of literary works of Mustofa Bisri is seen in the simplicity of the use of its poetic and aesthetic. The simplicity of the poetic and aesthetic means includes the elements of the structure of literary works and the manner in which they are expressed. The elements of the structure of literary works include typography, sounds, diction, images, and meaning. The simplicity of typography is seen in the freedom of the traditional ties and conventions of the theoretical structure of the poetical visualization. The simplicity of the sound is seen in the beauty, fusion, harmony, wholeness, and simplicity of its orchestration so it is more beautiful if Gus Mus's literary works are spoken. The simplicity of diction is seen in its attachment by clichés, classics, and bombastic, but in the election of words that are normally used to conversing and joking in everyday communication. The simplicity of his imagination is seen in the picture of wishful passage in and around the dwelling; next door neighbors, food stalls, markets, and everyday events: working, watching television, worshiping. The simplicity of meaning is seen in the reasonableness and calm it produces, namely the ability to dampen turmoil, not only the turmoil of body and soul, but also social unrest.